Enhancing Community-Based Renewable Energy Literacy Through University CSR Collaboration: A Comparative Study of UNPAB Indonesia and PTSS Malaysia - Sri Rahayu, Sri Rahayu; Elfitra Desy Surya; Rosasmanizan Binti Ahmad; Faisal (Yayasan Multidimensi Kreatif, 2025)
This study examines the role of university-led Corporate Social Responsibility (CSR) programs in enhancing community-based renewable energy literacy through a comparative analysis of Universitas Pembangunan Panca Budi (UNPAB), Indonesia, and Polytechnic Tuanku Syed Sirajuddin (PTSS), Malaysia. As the global transition toward sustainable energy accelerates, universities are increasingly expected to contribute to environmental education and community empowerment. Using a qualitative comparative case study approach, data were collected through interviews, documentation, and field observations of CSR activities conducted by both institutions. The findings reveal that CSR programs integrating renewable energy education significantly improve community knowledge, awareness, and practical skills related to solar energy, waste-to-energy systems, and energy conservation practices. The study also highlights differences in program design, stakeholder engagement, and implementation strategies between UNPAB and PTSS, shaped by institutional capacity and national energy policies. Furthermore, the research underscores the importance of cross-border academic collaboration in strengthening sustainable development initiatives. This study contributes to the discourse on CSR in higher education by offering a model for integrating renewable energy literacy into community-focused programs and providing strategic recommendations to enhance future CSR-based sustainability efforts.